Case Report: Persistent Strongyloidiasis Complicated by Recurrent Meningitis in an HTLV Seropositive Peruvian Migrant Resettled in Italy - Zammarchi, Lorenzo; Montagnani, Francesca; Tordini, Giacinta; Gotuzzo, Eduardo; Bisoffi, Zeno; Bartoloni, Alessandro; De Luca, Andrea (The American journal of tropical medicine and hygiene, 2015)
We describe a case of persistent strongyloidiasis complicated by recurrent meningitis, in a human T cell lymphotropic virus type 1 (HTLV-1) seropositive Peruvian migrant adult resettled in Italy. He was admitted with signs and symptoms of acute bacterial meningitis, reporting four other meningitis episodes in the past 6 years, with an etiological diagnosis of Escherichia coli and Enterococcus faecium in two cases. He had been previously treated with several antihelmintic regimens not including ivermectin, without eradication of strongyloidiasis, and he had never been tested for HTLV before. During the described episode, the patient was treated for meningitis with broad-spectrum antibiotic therapy and 200 pg/kg/dose oral ivermectin once daily on day 1, 2, 15 and 16 with full recovery and no further episodes of meningitis. The presented case underlines several critical points concerning the management of poorly known neglected diseases such as strongyloidiasis and HTLV infection in low-endemic areas. Despite several admissions for meningitis and strongyloidiasis, the parasitic infection was not adequately treated and the patient was not previously tested for HTLV. The supply of ivermectin and the choice of treatment scheme was challenging since ivermectin is not approved in Italy and there are no standardized guidelines for the treatment of severe strongyloidiasis in HTLV seropositive subjects.